Utah - Neri, P. J (New York Children's Press, 2002)
Describes the geography, history, government, people, and places of Utah
Introducing the Beehive State -- The land of Utah -- Utah through history -- Governing Utah -- The people and places of Utah -- Utah almanac -- Timeline -- Gallery of famous Utahns
Includes bibliographical references (p. 76) and index
Hurg
5
Keywords: Utah -- Juvenile literature; Utah